2013
DOI: 10.1614/wt-d-13-00066.1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Damage to Sensitive Landscape Plants from Wood Chips of Aminocyclopyrachlor Damaged Trees

Abstract: Applications of aminocyclopyrachlor in 2011 to turf resulted in brown and twisted shoots, leaves, and needles; shoot dieback; and in some cases, death of trees and ornamental plants adjacent to treated turf areas. Our research objective was to determine if a sensitive plant could be injured from wood chips (mulch) obtained from aminocyclopyrachlor-damaged trees, and to quantify movement of aminocyclopyrachlor from contaminated wood chips into soil and its subsequent uptake by roots into landscape plant tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…Similar reductions in ground ivy cover compared with an untreated check were observed when aminocyclopyrachlor was applied in either fall or spring (Patton et al, 2013b). Despite excellent ground ivy control, aminocyclopyrachlor is no longer registered for use in turf due to injury to nontarget vegetation (Patton et al, 2013a).…”
Section: Influence Of Herbicides and Mowing On Ground Ivy Covermentioning
confidence: 99%
“…Similar reductions in ground ivy cover compared with an untreated check were observed when aminocyclopyrachlor was applied in either fall or spring (Patton et al, 2013b). Despite excellent ground ivy control, aminocyclopyrachlor is no longer registered for use in turf due to injury to nontarget vegetation (Patton et al, 2013a).…”
Section: Influence Of Herbicides and Mowing On Ground Ivy Covermentioning
confidence: 99%
“…MT50 values of aminocyclopyrachlor were higher in sandy clay (1376 days), intermediate in loamy sand (1128 days), and lower in clay soil (877 days) (p < 0.05). The data regarding aminocyclopyrachlor mineralization recorded in this study indicate that the herbicide has a relatively long persistence in all soils and thus could provide prolonged weed control in drought years and this herbicide has high leaching potential, particularly in wet years, since Francisco et al reported that aminocyclopyrachlor was detected at all depths (0-30 cm) in the agricultural soils and can cause damage to sensitive plants, such as tomatoes [28], soybean, and beet [29].…”
Section: Aminocyclopyrachlor Mineralization To 14 Comentioning
confidence: 59%
“…However, Brecke et al (2010) reported centipedegrass to be tolerant (<20% injury) at rates as high as 0.20 lb a.i./acre. Registration of Imprelis within turfgrass has now ceased, due in part to the potential for damage to sensitive landscape plants (Patton et al, 2013). However, when used in range and pasture scenarios, results presented here indicate that aminocyclopyrachlor will effectively control common lespedeza.…”
Section: Discussionmentioning
confidence: 99%